The social gradient of obesity in Spain. What do we know and what should we know? (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
Introduction: WHO defines the social gradient as inequality in health along the continuum of socioeconomic status. Obesity is the result of multiple and complex causes and reflects a problem of social inequality. The objective of this article is to review and discuss available scientific evidence on the association between socioeconomic status (income, occupation, social class and education) and overweight / obesity in Spain in children and adults. Methodology: Critical review of the literature through PubMed and Econlit. Studies measuring the socioeconomic gradient of obesity in children and adults, published between 2000 and 2016.Results: 17 primary studies measuring the socioeconomic gradient of obesity in Spain have been reviewed, and another 8 that compare Spain with other countries. The mechanisms that explain the gradient are multiple and include less receptivity to messages and recommendations of primary prevention, less healthy eating patterns among children and adolescents of low socioeconomic status, and the obesogenic environment of low socioeconomic level households. To measure the gradient, the Absolute Inequality Index, the Relative Inequality index, the Concentration Index and the percentage attributable to the unfavorable socioeconomic level are used. Although the overall prevalence of obesity in adults seems to be stabilizing in Spain, there is a strong inverse social gradient by educational level and low socioeconomic status in both adults and children. Education is the most important inequality factor in any age group. Obese girls and women suffer from double discrimination, as the gradient is significantly higher for them than for the male gender.Conclusions: more studies are needed with high methodological quality and a long-term prospective design and objective measurement of body mass index to monitor trends and contribute to the design of effective policies against obesity, which are not only health policies but also policies enhancing equity.
Keywords: Obesity; socioeconomic factors; health inequality; social gradient.